Le charbon dans le Nord de la Belgique. - De Leener, Georges; Waxweiler, Emile; Wodon, L. (Bruxelles : Misch & Thron, 1904)
Collectie Vrijzinnige Werkmansbibliotheek
Frans
Monografie
Keywords: Vrijzinnige Werkmansbibliotheek